STRATEGI KOMUNIKASI RADIO REPUBLIK INDONESIA (RRI) JAKARTA DALAM MEMPERTAHANKAN PARA PENDENGAR (Analisis Pada Program Siaran Mimbar Agama Islam) - Misbach, Wahyu Misbach; Fitri, Annisa (Jurnal Cakrawala Ilmiah, 2024)
Wahyu Misbach, Annisa Fitri, “Republic of Indonesia (RRI) Jakarta Radio Communication Strategy in Retaining Listeners” Analysis of the Islamic Mimbar Broadcast Program. Islamic Communication and Broadcasting Study Program. This study aims to find out what communication strategies are used by RRI Pro1 Jakarta in broadcasting the Islamic Religious mimbar program. The research method used is descriptive method through a qualitative approach that takes data by making observations in the production room of RRI Jakarta, interviews and documentation and listening to the program under study. The results showed that RRI Pro1 Jakarta used three interrelated communication strategies in stages, namely the compatibility strategy by following the listener's needs and wants, the conformity-forming strategy by presenting the program at the same time and consistently so that the listeners are familiar with the existing broadcast schedule and the pull strategy. the masses by packaging promotions on various social media in an attractive form.